Exchange Rate Exposure and its Determinants: Evidence on Hungarian Firms - Lucie Tomanová (European Financial and Accounting Journal, 2014)
This paper analyses the foreign exchange rate exposure of Hungarian firms and its determinants on the basis of corporate cash flows and stock prices. The analysis focuses on the HUF/EUR exchange rate using monthly data from 2000 – 2014, resp. 2003 – 2012 in case of cash flow analysis. Stock prices exposure analysis showed that significant number of these firms is exposed: 18.4 % of publicly listed companies were significantly exposed in period 2007 – 2014 which is significantly higher than in previous period. According to the cash flow analysis results, 34 % of firms are exposed, whilst 45.3 % of small firms are significantly exposed. The measuring of exchange rate risk and hedging is therefore crucial for reduction of the firms' uncertainty. Cross-sectional analysis suggests that the turnover and foreign sales are also important determinants of firms' exchange rate exposure.
Keywords: C31; C32; F31; G32; 650; Stock prices; Exchange rate exposure; Cash flow